Corrupt practices : a Nigerian perspective - Ilorah, Peter (Abuja, Nigeria : The Regent Ltd., 2004)
An insight into the nature and areas of corrupt practices in Nigeria which traces the genesis of the evil of corruption to military incursions into politics in Nigeria.
"First published in March, 2004. Reprinted Jan. 2005"--t.p. verso.
Includes bibliographical references (p. 142-143).
oif 01/04/15
Loan
Keywords: Political corruption -- Nigeria; Nigeria -- Politics and government -- 1993-2007.